Desorption of water cluster ion from the surface of solid rare gases: Clusters - Tachibana, T.; Miura, T.; Arakawa, I. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2006)
Electron or photon irradiation on H2O adsorbed on the surface of rare gas solids induces the desorption of protonated water clusters, (H2O)nH+. The yield and the size n distribution of cluster ions depend on the coverage, the deposition temperature of water and the thickness of a rare gas film. These results indicate that the (H2O)nH+ ions are originated from the isolated water clusters and most important factor determining the size n distribution of desorbed (H2O)nH+ is the cluster size on rare gas solid. The measurement of kinetic energy distributions indicated that the desorbing energy of clusters depend on the rare gas species of the substrates and cluster size. It is suggested that the (H2O)nH+ desorption is due to Coulomb repulsion between the ionic water cluster and the rare gas ion.